Thermal management of urban subsurface resources - Delineation of boundary conditions. (2017) - Epting, Jannis
Abstract: Shallow subsurface resources are progressively used for the production of geothermal energy, i.e. for the installation and operation of a broad variety of Geothermal Energy Systems (GES). Additionally, in many urban areas there is a surplus of heat from large buildings and constructions reaching into the groundwater saturated zone. Likewise, groundwater is more often used as a cheap cooling medium. As a result, significantly increased subsurface temperatures have been observed in many urban areas. Several studies investigated how the so-called "Subsurface Urban Heat Island" (SUHI) effect and how current thermal subsurface regimes developed. However, a sustainable management of subsurface resources requires a general understanding on how "current thermal states" of subsurface and thermal regimes developed in context of different urban settings and boundary conditions. These aspects yet are mostly unexplored. In practice mitigation measures are generally taken for individual projects. Thereby, a consideration of the broader context of hydrogeological and thermal processes and boundaries and the interacting thermal activities could lead to a more sustainable use of subsurface energy resources. Besides providing an overview of subjects related to the thermal management of urban subsurface resources this review paper summarizes the results from different research projects that have been realized in the densely urbanised area of Basel in north-western Switzerland.